Formulasi Kebijakan Pola Pengasuhan Berbasis Hak Anak Pada Lingkungan Pendidikan Pondok Pesantren - Sulisman, Alya; Riswanda; Titi Stiawati (Sawala : Jurnal Administrasi Negara, 2024)
The formation of childcare regulations based on children's rights within the Islamic boarding school (pesantren) environment has become a crucial necessity in addressing the prevalent issue of violence against students (santri) in recent times. In the context of education, childcare based on children's rights is essential to ensure the protection, development, and optimal well-being of students, thereby creating a child-friendly educational environment in pesantren. By employing the library research method and a phenomenological approach derived from the researcher's experiences, this study explores the conditions of childcare patterns in pesantren, the differences in the characteristics of student care, and the urgency of establishing relevant regulations. The research findings indicate that a childcare pattern based on children's rights is urgently needed to prevent violence and ensure quality care provision within the pesantren environment. The government needs to take concrete steps in the formulation of such regulations by involving relevant stakeholders to ensure the sustainability and enhancement of the quality of education in pesantren while effectively safeguarding children's rights. This research is expected to contribute to the development of inclusive education policies that prioritize children's interests in Indonesia, particularly within pesantren contexts.